2017
DOI: 10.1007/s12070-017-1221-3
|View full text |Cite
|
Sign up to set email alerts
|

Dizziness in a Tertiary Care Centre in Sikkim: Our Experience and Limitations

Abstract: Dizziness is a common symptom and though most of the causes are benign yet some may be potentially life threatening. Diagnosis can be a challenge sometimes due to lack of dedicated vestibular lab and injudicious use of vestibular suppressant medications. A 2 year retrospective study of the hospital records from September 2014 to August 2016 was done to study the causes of dizziness and the limitations and challenges in the diagnosis. 75 complete records of patients presenting with dizziness were accessed and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…Similarly, in a study by Das et al, 41 of the total 75 patients were in the age group 21 to 40 years. 6 Similarly in another study by Prasad et al in 2018, 24.78% of the cases were in the age group of 40-49 years. 5 Kumar et al in 2018 reported maximum incidence of BPPV in 41-60 years age group.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Similarly, in a study by Das et al, 41 of the total 75 patients were in the age group 21 to 40 years. 6 Similarly in another study by Prasad et al in 2018, 24.78% of the cases were in the age group of 40-49 years. 5 Kumar et al in 2018 reported maximum incidence of BPPV in 41-60 years age group.…”
Section: Resultsmentioning
confidence: 73%
“…9 Das et al found BPPV as the commonest cause of vertigo, diagnosed in 20% of the cases presenting with dizziness. 6 In a study by Breven et al, BPPV was reported in 8% of the cases. 5 The incidence of vertigo noted in our study was seen maximum in age group 46 to 60 years (36.89%) followed by 31 to 45 years age group (31.28%) with minimum no.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Most of the articles originated from India (n = 17, 65.4%) ( Anshul et al., 2020 ; Ashish et al., 2017 ; Bansal, 2016 ; Das et al., 2017 ; Dash et al., 2008 ; Haripriya et al., 2021 ; Lepcha et al., 2014 ; Mamindla et al., 2020 ; Prakash et al., 2008 , 2021 ; Prakash and Shah, 2009 ; Sen et al., 2016 ; Sunitha et al., 2019 ; Swain et al., 2018 , 2020 ; Syed et al., 2020 ; Udagatti and Dinesh Kumar, 2017 ), followed by Egypt (n = 3, 11.5%) ( El-Badry et al., 2017 ; ElSherif et al., 2020 ; Mostafa et al., 2014 ), Nigeria (n = 3, 11.5%) ( Adegbiji et al., 2014 ; Ogah, 2017 ; Olusesi and Abubakar, 2016 ), Iran (n = 1, 3.8%) ( Taghdiri et al., 2014 ), Tunisia (n = 1, 3.8%) ( Mouelhi et al., 2020 ), and Vietnam (n = 1, 3.8%) ( Ky et al., 2021 ) as represented by the heat map ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Vertigo yang disebabkan oleh penyakit di sistem saraf pusat memiliki prevalensi 3.2-12.5% dari keseluruhan pasien yang datang ke UGD (6). Dari semua pasien yang datang ke UGD dengan vertigo, sebanyak 4% disebabkan oleh karena penyakit di serebelum, 1.3% penyakit di fossa posterior, dan 14.7% disebabkan oleh penyakit jantung dan metabolik (7).…”
Section: Epidemiologiunclassified